Rediscovery of the rare ant genus Bannapone (Hymenoptera: Formicidae: Amblyoponinae) and description of the worker caste - Guénard, Benoit; Blanchard, Benjamin; Liu, Cong; Yang, Da-Rong; Economo, Evan (Zootaxa, 2013)
The genus Bannapone was described in 2000 on the basis of a single dealate queen specimen. Since its original collection in Yunnan, China, no other specimen has been reported, making it one of the rarest ant genera in the world. Here we report the collection of two workers of Bannapone also from Yunnan province. The description of the worker caste is presented. Furthermore, we found significant differences with the described B. mulanae Xu, 2000 which leads us to describe the workers as a new species, B. scrobiceps n. sp.. Finally, we briefly discuss the importance of leaf-litter collection methods to collect taxa considered as “rare”.